Evaluation of Released Cashew Varieties under Odisha Condition - Tripathy, P.; Sethi, Kabita; Mukherjee, S. K. (International Journal of Bio-resource and Stress Management, 2023)
In order to address the challenge of poor nut yield of present cashew plantations in India, a trial consists of twenty five released varieties of cashew from different parts of India was laid out during 2008 under RBD with two replications having six plants treatment-1. The results recorded over two years namely 2013 and 2014 revealed significant variations among the varieties for vegetative growth, nut yield attributing parameters and nut yield. The cashew varieties such as Amrutha, BPP-4, Madakathara-2, K-22-1, VRI-3, Ullal-4, UN-50 and Goa-1 were identified for dwarf plant architecture, due to their cumulative plant height (2.58 to 4.05 m) and canopy spread area (7.78 to 16.67 m2) at 6th and 7th year of planting, which need further evaluation. Similarly, both Priyanka and Dhana can be exploited for cashew apple processing purpose due to their large and heavy cashew apples (68.00 to 76.50 g). The shelling % demonstrated by majority of the varieties was within the acceptable International Standard of more than 28.00%. The cashew varieties namely BPP-8, Vengurla-7, Bhaskara, NRCC Sel-2, Ullal-3, Kanaka, Vengurla-4, Bhubaneswar-1, VRI-3 and Dhana combined two or three traits which were significantly different from rest of the varieties evaluated. However, cashew varieties such as BPP-8, Vengurla-7, Bhaskara, NRCC Sel-2 and Ullal-3 seem outstanding for most of the parameters considered namely trunk girth (34.73-54.40 cm), canopy spread area (12.06-37.73 m2), nut weight (7.45-10.10 g), nut yield plant-1 (4.00-6.05 k) and cumulative nut yield (8.011.86 k plant-1) at 7th year of planting.